Organizing Integration in the Swedish Labor and Housing Markets - Susanne Urban; Emma Holmqvist; Vedran Omanović (Nordic Journal of Migration Research)
Policies for refugees’ settlement, housing, and employment are usually not formulated or analyzed in relation to each other. This study aims to address the dialectical relationship among settlement, housing, and labor market activation policies for refugees. To do this, we draw on Benson’s (see Benson 1977; 1983) conceptualization of the dialectical perspective and its four interconnected principles (social construction/production, context, contradiction, and praxis) and employ this approach at two critical moments when Swedish policies on housing and employment for refugees were significantly reorganized. Overall, the organization of the settlement and inclusion of refugees in terms of housing and employment produces intentional and unintentional contradictions with several possible outcomes. The actual outcomes show that some contradictions and paradoxes among the various spheres and geographical levels have not been resolved by state policy reorganization (decentralization or centralization).